The girl from Venice [compact disc, unabridged] : a novel - Smith, Martin Cruz, 1942- (Simon & Schuster Audio, 2016)
A poor fisherman named Cenzo comes across a girl's body, floating in the lagoon. He carries her into his boat and soon discovers that she is very much alive, and very much in trouble. Born to a wealthy Jewish family who has been captured and deported by the Nazis, Guilia is on the run after she was found hiding in a local hospital. Cenzo decides it's the right thing to do to help her escape, never anticipating an innocent act of chivalry would quickly turn to love as the two grow closer.